2019
DOI: 10.24036/0201932104918-0-00
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity Test of Cinnamon Extract (Cinnamomun burmani) on Growth of Aspergillus flavus and Fusarium moniliforme

Abstract: The purpose of this research is to determine the activity of cinnamon extract (Cinnamomun burmani) as an antifungal against the growth of fungi Aspergillus flavus and Fusarium moniliforme. The procedure begins with making cinnamon extract obtained from cinnamon bark using rotary distillation method. Cinnamon extract will be tested using different concentrations of 0% (control); 0,5%; 1,0%; 2,0% and 4,0% with the well diffusion method. Based of the results, the cinnamon extract has antifungal activity against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…The method of Novrianti et al [40] used in the antifungal activity test was the well diffusion method of pour plate culture-grown A. flavus FRR3961 obtained from Food and Nutrition Culture Collection, Center for Food and Nutrition Studies Universitas Gadjah Mada, Indonesia. Prior to the antifungal test, the initial microorganism was calculated for each native yeast and A. flavus using the McFarland 0.5.…”
Section: Antifungal Activity Test Towards a Flavusmentioning
confidence: 99%
“…The method of Novrianti et al [40] used in the antifungal activity test was the well diffusion method of pour plate culture-grown A. flavus FRR3961 obtained from Food and Nutrition Culture Collection, Center for Food and Nutrition Studies Universitas Gadjah Mada, Indonesia. Prior to the antifungal test, the initial microorganism was calculated for each native yeast and A. flavus using the McFarland 0.5.…”
Section: Antifungal Activity Test Towards a Flavusmentioning
confidence: 99%
“…With these inhibition zone diameters, the cinnamon extract received a very strong inhibitor extract category (Novrianti et al, 2019). Observations from in vitro tests have also shown that cinnamon leaf extract significantly inhibited the fungal colony growth, biomass, and spore formation.…”
Section: Introductionmentioning
confidence: 97%